2023
DOI: 10.1186/s12885-023-10755-z
|View full text |Cite
|
Sign up to set email alerts
|

Pan-cancer analysis and experimental validation of DTL as a potential diagnosis, prognosis and immunotherapy biomarker

Abstract: Background DTL has been found to be related with multiple cancers. However, comprehensive analyses, which identify the prediction value of DTL in diagnosis, prognosis, immune infiltration and treatment, have rarely been reported so far. Methods Combined with the data online databases, the gene expression, gene mutation, function enrichment and the correlations with the immunity status and clinical indexes of DTL were analyzed. Expression of DTL and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 44 publications
0
2
0
Order By: Relevance
“…Additionally, on the basis of correlation analysis of the genes included in the follow‐up immunological examination, effective immunotherapy outcomes were anticipated. 43 Thus, given the significance of immunotherapy in the management of malignant tumors, targeting DTL might provide us with fresh perspectives on OS therapy. EXO1 plays a key role in protecting genome stability during DNA replication and post‐replication processes; further, it participates in and plays important roles in various DNA repair processes.…”
Section: Discussionmentioning
confidence: 99%
“…Additionally, on the basis of correlation analysis of the genes included in the follow‐up immunological examination, effective immunotherapy outcomes were anticipated. 43 Thus, given the significance of immunotherapy in the management of malignant tumors, targeting DTL might provide us with fresh perspectives on OS therapy. EXO1 plays a key role in protecting genome stability during DNA replication and post‐replication processes; further, it participates in and plays important roles in various DNA repair processes.…”
Section: Discussionmentioning
confidence: 99%
“…Denticleless E3 ubiquitin protein ligase homolog (DTL) is overexpressed in BCa, and increased DTL expression correlates with malignant biological behavior and promotes BCa progression through the AKT/mTOR pathway ( 61 ). A pan-cancer study also showed that DLT could be a potential immunotherapy biomarker ( 106 ).…”
Section: Roles and Mechanisms Of E3 Ubiquitin Ligases In Bladder Cancermentioning
confidence: 99%